IMPLEMENTASI STRATEGI TALENT ACQUISITIONS - Putra, Reynaldi Sudarno; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Talent of War has impacted various industry sectors around the world, including technology companies where the quality of business operations and products are highly influenced by the talent they have. Therefore, PT.X, one of the largest technology companies in Indonesia, is very concerned about the implementation of an effective talent management strategy, especially in the talent acquisitions department in order to compete in getting the best talent. This research aims to analyze the implementation of PT.X's Talent Acquisitions strategy. This research uses a qualitative case study approach. The results showed that PT.X has implemented the recruitment strategy and talent mapping to talent acquisitions well. PT.X also utilizes technology and digital tools to support the process. However, PT.X still needs to maximize the talent acquisitions function, especially to reduce the recruitment time which is still fairly long. This research provides insight into the implementation of Talent Acquisitions strategies in technology companies in Indonesia. The results of this study are expected to help other companies in improving their talent management and development.